Women’s Peace and Love: Gender-Based Violence in Woodstock and Palomita Blanca (Anclajes, 2020)
From the analysis of cultural productions that valued “peace and love,” such as Woodstock and Piedra Roja, represented in the novel Palomita Blanca (Lafourcade) and the namesake film by Raúl Ruiz, the present work questions the alleged suicides by overdose or out of love committed by female artists as well as the addictions they have faced as responses to sustained gender violence. Hence, it is concluded that just as art reproduces and promotes violence against women, it can also be an agent that enables a new agreement and understanding of the violence that they would supposedly exercise against themselves.
Keywords: female artists; romantic love; gendered violence